Validity Of Tam Over A Period Of Time: A Sensemaking Perspective - Bushra, Aafaqi (Universiti Sains Malaysia, 2003)
Technology adoption is being talked of more frequently now as compared to ten fifteen years back. It is because today the major thrust of organization's competitiveness is in their ability to employ new technology in their day-to-day tasks. This study was carried out to investigate if sensemaking activities influence technology acc ptance model (TAM) and if the strength of relationship between TAM's constructs changes over a period of time. This study was a panel-based longitudinal study, whereby data were collected in three stages in one semester.